Factors affecting the provision of health service delivery in schools in Engela district, Ohangwena region, Namibia - Daniel O. Ashipala; Miina Shapopi (AOSIS, 2022)
Background: While health services have been offered at various schools in Namibia since independence in 1990, coverage has been limited and there has been a notable decline in recent years. This reduction of services is of great concern, with questions being raised regarding what factors are affecting the provision of these services. Aim: To explore the factors affecting the provision of health services to schools in Engela district, Ohangwena region, Namibia. Settings: Semistructured interviews were conducted at a public health care facility situated in the northern part of Namibia. Methods: A qualitative, explorative, descriptive and contextual research design was utilised. Data were collected through semistructured interviews with 15 nurses from a health centre, of whom five were enrolled nurses and 10 were registered nurses. The data were then analysed thematically. Results: The study revealed three themes: participants' understanding of school health services; factors affecting the delivery of school health services; and corrective measures for improving the delivery of school health services. Conclusion: The notable decline in health service provision to various schools within the district suggests that there might be factors affecting the provision of school health services, posing a serious challenge to the active implementation of the School Health Programme. Contribution: These findings could be used to make adjustments to the provision of school health services and will also serve as an information baseline to elicit suggestions for future research related to school health services.